Incident gout and erectile dysfunction: is hyperuricaemia the elephant in the room? - Abhishek, Abhishek; Doherty, Michael (BioMed Central, 2017)
The first prospective population-based study to examine risk of erectile dysfunction in men with gout in the western world has been published. It reports that following their first diagnosis of gout, men have a 31% higher risk of erectile dysfunction than matched controls, although the absolute increase in risk is small. Of interest, the incidence of erectile dysfunction reported in this study is tenfold higher than those reported in nation-wide cohort studies from Taiwan. There is a need for further prospective cohort studies to examine the possible mechanistic association between gout, hyperuricaemia and erectile dysfunction.